PEMBUATAN KOMPOSIT BERPORI TINGGI UNTUK BIOMATERIAL - Soeswanto, Bambang (KINETIKA, 2019)
One application of biomaterials in the medical field is the manufacture of guided bone regeneration (GBR) membranes to help bone regeneration. The GBR membrane can be synthesized from polycaprolactone (PCL), which is a biocompatible polymer and can be absorbed by human body. The aim of this research is to obtain the composition of PCL, hydroxyapatite, and NaCl as well as the pressure on the composite printing to obtain high porosity GBR. Deficiencies in PCL properties such as slow degradation, poor mechanical properties, and low cell adhesion will be improved by adding porous NaCl to obtain porous composites and Hydroxyapatite to limit the porogen extraction process. Pressure printing of membranes will improve the mechanical properties of composites and the homogeneity of pore size. The results showed that higher compression obtained products with high porosity, namely for 79-97% at a pressure of 15 MPa and 75- 95% at a pressure of 20 MPa. While the SEM test showed that the pore size varied between 103.769 – 140.911 μm, 13.2 – 28.026 μm, and 1.503 – 4.718 μm